1984
DOI: 10.1002/bip.360230905
|View full text |Cite
|
Sign up to set email alerts
|

Reversing‐pulse electric birefringence of poly (γ‐benzyl‐L‐glutamate). II. Field‐strength dependence of steady‐state and decay signals of well‐fractionated samples

Abstract: SynopsisThe electric field dependence (up to 21 kV/cm) of the steady-state and decay signals has been examined on the four well-fractionated samples of poly(y-b~nzyl-L-glutamate), [Glu(OBzl) and field-free relaxation time were analyzed by a method that takes into account the polydispersity of the chain length. The weight-average chain length, ( ltJ, permanent dipole moment, (p,, 1, electric polarizability anisotropy, (Aa, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…is that the electric field orientation mechanism can be identified by inspecting a single RPEB signal with reference to theoretical predictions.28 Serious attempts were, however, made only recntly on the quantitative interpretation of experimentally observed RPEB signals to evaluate the electrooptical and hydrodynamic properties of nonconducting helical polypeptides in solution which are polydisperse regarding their lengths. [29][30][31][32][33] In this analysis, the feature of the reverse portion in RPEB signals, i.e., the extremum (a dip or a hump) and the time required to reach it, was utilized in the low-field region, together with the steady-state birefringence and the field-free relaxation time in the decay portion measured over a wide range of field strengths.…”
Section: Introductionmentioning
confidence: 99%
“…is that the electric field orientation mechanism can be identified by inspecting a single RPEB signal with reference to theoretical predictions.28 Serious attempts were, however, made only recntly on the quantitative interpretation of experimentally observed RPEB signals to evaluate the electrooptical and hydrodynamic properties of nonconducting helical polypeptides in solution which are polydisperse regarding their lengths. [29][30][31][32][33] In this analysis, the feature of the reverse portion in RPEB signals, i.e., the extremum (a dip or a hump) and the time required to reach it, was utilized in the low-field region, together with the steady-state birefringence and the field-free relaxation time in the decay portion measured over a wide range of field strengths.…”
Section: Introductionmentioning
confidence: 99%
“…For rigid cylindrically symmetric molecules with a permanent dipole moment along the symmetry axis at low fields and degrees of orientation, Ueda et al 27) and O'Konski 1) have shown that Dn becomes…”
Section: Governing Equationsmentioning
confidence: 99%